The Effect of Using a Virtual Laboratory Based on PhET Simulation to Improve the Higher Order Thinking Skills of Class X Science Students - vani, Agustina Stevania Bejo (Lembaga Riset Mutiara Akbar, 2023)
Physic Education and Technology Simulation is a learning media in the form of interactive multimedia-based computer software in the form of a series of laboratory equipment that simulates laboratory activities such as the use of appropriate practicum media by the user. To find out the effect of the use of phed-based virtual laboratories on the high level of thinking ability of class X IPA students is the purpose of this study, with 25 student samples. Purposive sampling technique is a sampling method in this study. This research is a type of quantitative research. The Quasi Experiment Method is the method used in this study, by way of Nonequivalent Control Group Design which includes two classes namely the control class and the experimental class where this is randomly chosen from the sample of two classes. The data collected is obtained by giving pre-test questions and post-test high-level thinking skills. N-Gain testing is a technique used to analyze data. The results of the study referring to the N-Gain calculation showed that the experimental class was higher than the control class. High-level thining skills increased by 59 % in the experimental class and 12 % in the control class. Based on the results og N-Gain calculations, students’ high-level thinking skills increase after using PhET for learning simulations